Knowledge, Attitude and Practices towards Oral Hygiene among Adults (18-45yrs) in Lira Regional Referral Hospital, Lira City. A Cross-sectional Study. - Henry Okello; Vincent Charles Kalungi (Student's Journal of Health Research Africa, 2022)
Background: